Social tourism as a modest, yet sustainable, development strategy: policy recommendations for Greece - Kakoudakis, Konstantinos I.; McCabe, Scott (Taylor & Francis, 2018)
Recent findings from social tourism research and evidence from its practice have shown that social tourism has multiple benefits, both for individual participants and host-communities within destinations. The latter in particular have been acknowledged by the European Union and have been included in its recent sustainable tourism policy. Yet, there are a limited number of studies that have attempted to explicate the close linkages between social tourism and sustainable development, and to inform public policy. This paper aims to do so with specific reference to Greek social tourism programmes. Drawing upon development theory, specifically sustainable development, and sustainable tourism research in particular, the study builds an argument for the potential of social tourism to act as a stabilising force in the Greek tourism system, contributing to the achievement of sustainability outcomes for host-communities. In doing so, the paper makes tangible policy recommendations, which are also timely, given the current socioeconomic environment that has been shaped in Greece, across Europe, and elsewhere, since the 2008 crisis.